Kemampuan Berbicara Anak Berkebutuhan Khusus: Studi Kasus Anak Tunagrahita di SLB PK & PLK - Nur, Asriani (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
This study aims to determine the vowels and consonants of mentally retarded children capable of light level VII grade students at SLB PK & PLK Galesong when speaking. The subjects of this study were 16 mentally retarded students who were in SLB PK & PLK Galesong but the object was grade VII students at SLB PK & PLK Galesong mentally retarded, amounting to 5 people. The method in this research is the descriptive method. The instruments used were observation, record,ing and take notes. then to find out the results of the mental retardation ability of children is used a suitable checklist or checklist in the form of indicators of the speech ability of mentally retarded children. The results showed that the acquisition of data known number of students with data 001 amounted to 50, 002 amounted to 63, 003 amounted to 53, 004 amounted to 43 while Data 005 got a value of 30, thus the results of the average speech ability of mentally retarded students capable of light level students in SLB Galesong PK & PLK of 48. From that it can be concluded that mentally retarded students capable of mild level of education are in the category lacking in speaking ability because of the many phonemes and phonemes both vocal and consonant changes.